“WORDS ARE BUT WIND”: THE PROVERBS AND PRO-VERBIAL EXPRESSIONS OF BOB DYLAN - Summerville, Raymond (Proverbium - Yearbook, 2019)
This essay examines the use of proverbs and proverbial language in the music and life of Bob Dylan. Through the lens of paremiology, it explores current Dylan scholarship including: biographies, literary studies, Dylan interviews, and his extensive catalogue of music in order to understand the way that proverbs and proverbial expressions influence his work and audiences. It also explores the extent that they also reflect his life experiences and philosophical viewpoints.